Impact of extreme rainstorm on the spatial distribution of population exposure in Haihe River basin in China - C. Cheng; X. Fang; S. Zhang; Y. Yu; S. Yang; Y. Li; J. Liu; C. Mei (International Journal of Environmental Science and Technology, 2026)
Based on daily rainfall data from 252 national meteorological stations in the Haihe River Basin of China during 1961–2023, rainstorm events were divided, and four characteristic variables representing the hazard index of rainstorms were statistically analyzed, including total number of rainstorm days ( I day ), cumulative rainfall ( I pre ), average daily rainfall ( I 24pre ), and maximum duration days ( I dur ). Combined with the 1 km gridded population density data of the basin, the population exposure ( PE ) during 1961–2023 under scenarios with and without the “23·7” extreme rainstorm was calculated using the product model of the rainstorm hazard index ( HR ) and exposed population. K-means clustering was adopted to analyze the impact of this rainstorm on the spatial distribution characteristics of watershed population exposure, and a quantitative assessment of the impact contribution rate ( PEC ) was provided. The results show that a single extreme rainstorm can cause changes in the spatial clustering of population exposure in nearly 1/3 of the districts and counties in the basin, and its contribution rate to rainstorm hazard index and population exposure can exceed 10%, which provides a scientific basis for the timely incorporation of typical extreme rainstorm cases and the updating of the flood control and drainage design assessment system as well as relevant codes and standards. The findings can also help optimize the layout of flood storage and detention areas, and provide references for the deployment and construction of X-band radars in areas along the front plain of the Taihang Mountains.